Conduction disturbances after TAVR: rates of pacemaker implantation, burden of ventricular pacing and prognostic significance. (24th May 2021) - Bricoli, S; Benatti, G; Vignali, L; Tadonio, I; Notarangelo, MF; Crocamo, A; Gonzi, G; Placci, A; Bottoni, N; Biagi, A; Rossi, L; Guiducci, V; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: The occurrence of conduction disturbances remains frequent after TAVR. However, the effect of PM on mortality is controversial and many patients may recover spontaneous AV conduction during follow-up. PURPOSE: To evaluate the incidence of PM implantation after TAVR, PM dependency and burden of ventricular pacing during follow-up and their influence on mortality. METHODS AND RESULTS: We performed a retrospective analysis of all consecutive 293 patients who underwent TAVR from 2015 to 2019 at our hospital, regional hub for this procedure. Patients were classified into 3 groups: patients without PM (no-PM), patients with a PM implanted prior to TAVR (pre-PM) and patients requiring a PM following TAVR (post-PM) and their clinical and procedural characteristics are listed in Table 1. The rate of PM implantation after TAVR was 20, 8%, at a median of 3.6 days after the procedure. The most common indication was complete AV block. A VVIR pacemaker was implanted in 28 patients, a DDD/DDDR PM in 27 patients and 2 patients received a CRT device. Among post-PPM patients, only 16% were PM-dependent at 2-month and 1-year follow-up. All of them received a PM for complete AV block (AVB). At 1-year follow-up, RV pacing burden was 60% among AVB patients and 23% in patients with a PM implanted for other reasons. PM implantation after TAVR was not associated with a mortality difference at 30-day, 1-year and long-term follow-up. Pre-PPM patients showed a higher mortality rate at long-term follow-up although not statistically significant. CONCLUSIONS: Our data suggest that a single chamber device should be preferred in patients implanted for reasons other than complete AVB; in patients with AVB, the use of dual chamber device with an algorithm to minimize RV pacing should be the most suitable choice.